2016
DOI: 10.1073/pnas.1604692113
|View full text |Cite
|
Sign up to set email alerts
|

Exoplanet orbital eccentricities derived from LAMOST–Kepler analysis

Abstract: The nearly circular (mean eccentricity e ≈ 0.06) and coplanar (mean mutual inclination i ≈ 3°) orbits of the solar system planets motivated Kant and Laplace to hypothesize that planets are formed in disks, which has developed into the widely accepted theory of planet formation. The first several hundred extrasolar planets (mostly Jovian) discovered using the radial velocity (RV) technique are commonly on eccentric orbits ( e ≈ 0.3). This raises a fundamental question: Are the solar system and its formation spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
224
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 254 publications
(256 citation statements)
references
References 34 publications
(21 reference statements)
22
224
3
1
Order By: Relevance
“…The mean, median and their 1-σ uncertainties is determined by bootstrapping the single planet population for 1000 realizations. This is slightly higher than the estimated value by Xie et al (2016), which it might be expected, since the observed single transit planet systems are likely to be a mixture between the single super-Earths and the multiple superEarths systems with relatively high mutual inclinations, which have lower eccentricities.…”
Section: Eccentricities and Inclinations Of Super-earthscontrasting
confidence: 55%
See 3 more Smart Citations
“…The mean, median and their 1-σ uncertainties is determined by bootstrapping the single planet population for 1000 realizations. This is slightly higher than the estimated value by Xie et al (2016), which it might be expected, since the observed single transit planet systems are likely to be a mixture between the single super-Earths and the multiple superEarths systems with relatively high mutual inclinations, which have lower eccentricities.…”
Section: Eccentricities and Inclinations Of Super-earthscontrasting
confidence: 55%
“…The bulk of these low mutual inclination systems have similar properties as the Kepler multiple systems, which are much more circular and coplanar, with an upper limit to the mean eccentricity of ∼ 0.07 (Xie et al 2016).…”
Section: Eccentricities and Inclinations Of Super-earthsmentioning
confidence: 94%
See 2 more Smart Citations
“…Assuming a moderate eccentricity e=0.1 of ProximaCen-taurib (Xie et al 2016;Brown 2017), we simulate the strengths of its TTVs perturbed by an outer planet with varying masses and orbital periods in coplanar orbits. The mass and orbital period of the outer planet are constrained by the requirement that the Doppler reflex stellar RV should be <3 m s −1 to keep the planet undetectable in the high-precision observation of Anglada-Escudé et al (2016).…”
Section: Comparing With the Candidate Transit Events In Most Datamentioning
confidence: 99%